Oil and gas presence perspectives of weathering layer reservoir of Nurol'ka mega-basin according to data of geothermics; IOP Conference Series: Earth and Environmental Science; Vol. 43 : Problems of Geology and Subsurface Development - Luneva T. (Petroleum Geology: Current Exploration and Extraction Methods, 2016)
Title screen